Integrating Community-Based Ecotourism into Educational Development: Empowering Local Communities and Enhancing Sustainable Practices - Mufidatul Himmah; Ratih Ika Wulan Dari Laila (Al-Qalam Institue, 2025)
This study examines the development of coastal community-based ecotourism in Probolinggo Regency and its impact on local community empowerment and income generation. The research employed a descriptive qualitative method, with data collected through observation, interviews, and documentation. The results indicate that local communities are actively involved in ecotourism through homestay management, local guides, traditional food production, and environmental conservation. Village institutions such as Village-Owned Enterprises (BUMDes) and Tourism Awareness Groups (Pokdarwis) play a crucial role in facilitating training and participation. Consequently, the community's monthly income increased by between IDR 500,000 and IDR 1,500,000, as well as a greater awareness of environmental and cultural preservation. Theoretically, this study contributes to educational development, particularly in community education and lifelong learning. It highlights how informal and non-formal education through training, mentoring, and hands-on experience can effectively empower rural communities. Ecotourism serves as a tangible learning space that promotes civic responsibility and the values of sustainable development. For educational institutions, these findings emphasize the importance of integrating community-based practices into the curriculum, particularly in the areas of tourism, environmental studies, and citizenship education, to strengthen the link between formal education and community empowerment efforts.